2002
DOI: 10.1093/nar/gkf418
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 113 conserved essential genes using a high-throughput gene disruption system in Streptococcus pneumoniae

Abstract: The recent availability of bacterial genome sequence information permits the identification of conserved genes that are potential targets for novel antibiotic drug discovery. Using a coupled bioinformatic/experimental approach, a list of candidate conserved genes was generated using a Microbial Concordance bioinformatics tool followed by a targeted disruption campaign. Pneumococcal sequence data allowed for the design of precise PCR primers to clone the desired gene target fragments into the pEVP3 'suicide vec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
177
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(186 citation statements)
references
References 33 publications
8
177
0
1
Order By: Relevance
“…Because streptococci have limited biosynthetic capacities, the products of these operons may be involved in the uptake of essential nutrients. Indeed, it has been shown that one of the cbiO orthologs (ybaE) is an essential gene in Streptococcus pneumoniae (16). It was tempting to speculate that single bioY genes encode functional biotin transporters.…”
Section: Discussionmentioning
confidence: 99%
“…Because streptococci have limited biosynthetic capacities, the products of these operons may be involved in the uptake of essential nutrients. Indeed, it has been shown that one of the cbiO orthologs (ybaE) is an essential gene in Streptococcus pneumoniae (16). It was tempting to speculate that single bioY genes encode functional biotin transporters.…”
Section: Discussionmentioning
confidence: 99%
“…Several genome-wide inactivation studies have been carried out to identify essential genes in different bacterial species. Targeted gene disruptions have been used in Escherichia coli (Arigoni et al, 1998;Freiberg et al, 2001) and Streptococcus pneumoniae (Thanassi et al, 2002;Zalacain et al, 2003). Transposon mutagenesis in Haemophilus influenzae (Akerley et al, 2002) and Mycoplasma sp.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Listeria monocytogenes lacks the ability to synthesize thiamin and depends on an ECF transporter for the uptake of this essential micronutrient 15 . In other clinically relevant bacteria, such as Mycoplasma genitalium, Streptococcus pneumoniae and Staphylococcus aureus, the genes that encode ECF transporters are also essential [16][17][18][19][20] , probably because these organisms lack the pathways for folate, biotin and thiamin biosynthesis, respectively (Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway database). These examples highlight the importance of ECF transporters and suggest that the proteins involved are potentially useful targets for novel antibiotics.…”
mentioning
confidence: 99%